GIRISH KARNAD’S THEATRICAL VISION: GENDER, POWER, AND IDENTITY IN MODERN INDIAN DRAMA - Patteti, Raja Sekhar; Yadagiri, G (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper critically examines the selected plays of Girish Karnad, one of India's most distinguished playwrights, focusing on themes such as gender, identity, power, and social justice. The research delves into Karnad's exploration of traditional and contemporary issues through the lenses of Indian mythology, history, and cultural discourse. Plays like Yayati, Tughlaq, Hayavadana, Naga-Mandala, and Tale-Danda are analyzed to highlight Karnad's nuanced portrayal of gender binaries, the complexities of leadership and reform, the tension between tradition and modernity, and the struggle for individual agency in a patriarchal society. In Yayati, the play challenges gender norms, especially through the strong and independent character of Devayani, while Tughlaq offers a critique of post-colonial India’s political and social realities. Hayavadana explores gender consciousness and identity, while Naga-Mandala provides a poignant commentary on women’s empowerment in a traditional society. Tale-Danda weaves the symbolic tension between modernity and tradition in rural India. Through these plays, Karnad critiques both societal and political structures, offering a complex, multifaceted view of India’s historical and contemporary challenges. This research underscores the enduring relevance of Karnad's work in addressing issues of gender, power, and identity within the Indian socio-political context.